Valorization of Rambutan Peel as Adsorbent for Tempeh Wastewater - Dewi Kurnianingsih Arum Kusumahastuti; Rindang A Laksono; Ronal F Hindra (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Tempeh is one of Indonesia traditional foods which made from fermentation processed soybean. There is wastewater from tempeh production that usually wasted to the river without further treatment. One of the parameters for wastewater is chemical oxygen demand (COD). Higher COD correlated to the higher risk to the environment. To decrease the COD level of tempeh wastewater valorization rambutan peels as adsorbent was done. The adsorbent was prepared by drying up and powdering rambutan peels. Boehm titration was used to characterize some functional groups of rambutan peels. Optimization of the contact time and the acidity level (pH) was done under room temperature condition. As results, the rambutan peel contains carbocyclic (0,0492%), alkaline functional group (0,0360%), phenol (0,0004%) and lactone (0,0002%). Besides, the optimal condition for the reaction were at pH 11 for 90 minutes that can reduce COD level from 23.840 mg/L to 10.230 mg/L.